2016
DOI: 10.1007/s13312-016-0840-1
|View full text |Cite
|
Sign up to set email alerts
|

Clitoral length and anogenital ratio in Indian newborn girls

Abstract: The normative values generated can serve as reference standard in the assessment of clitoromegaly, ambiguous genitalia, virilizing effects and suspected in utero androgen exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 12 publications
1
17
0
1
Order By: Relevance
“…A shorter AGDas and penile length have been found in infants with hypospadias and cryptorchidism, a longer AGDaf has been described in female infants with androgen excess, for example, in congenital adrenal hyperplasia (CAH). In typical female infants, it was shown that calculating the anogenital-ratio (AGDaf:AGDac) offers advantages as it follows a normal distribution and does not correlate with anthropometric variables or gestational age (19,20). The Prader score (PS) was developed by Andrea Prader in 1954 to capture genital variation in children who have CAH.…”
mentioning
confidence: 99%
“…A shorter AGDas and penile length have been found in infants with hypospadias and cryptorchidism, a longer AGDaf has been described in female infants with androgen excess, for example, in congenital adrenal hyperplasia (CAH). In typical female infants, it was shown that calculating the anogenital-ratio (AGDaf:AGDac) offers advantages as it follows a normal distribution and does not correlate with anthropometric variables or gestational age (19,20). The Prader score (PS) was developed by Andrea Prader in 1954 to capture genital variation in children who have CAH.…”
mentioning
confidence: 99%
“…Our MCL was also similar to that of other studies that involved preterms, including the 3.66 ± 0.13 mm reported by Riley and Rosenbloom [13] in black term and preterm newborns in United States. Mondal et al [20] also reported a comparable albeit slightly lower MCL of 3.1 ± 1.54 mm in India and Jarrett et al [19] reported a relatively higher MCL of 7.7 ± 1.37 mm in 244 term and preterm newborns in Nigeria.…”
Section: Discussionmentioning
confidence: 97%
“…Some studies included preterms [13, 19, 20] whereas this study recruited only term newborns. Clitoral size has also been reported to correlate with anthropometric parameters of the study population [10].…”
Section: Discussionmentioning
confidence: 99%
“…As far as the authors are concerned, the present study is the first to investigate the clitoral size in newborn females in Iran, and very few similar studies in Middle East has been undertaken. Normative clitoral size data for healthy term newborns have been reported sparsely from different Asian and Caucasian infants (12)(13)(14)(15)(16). Also, only few studies are available, conducted on both term and preterm infants (12,16).…”
Section: Introductionmentioning
confidence: 99%
“…Normative clitoral size data for healthy term newborns have been reported sparsely from different Asian and Caucasian infants (12)(13)(14)(15)(16). Also, only few studies are available, conducted on both term and preterm infants (12,16). Thus, this study was performed to establish mean and standard deviation (SD) values of CL and CW of Iranian term and preterm newborns in relation to gestational age (GA) and anthropometric measurements.…”
Section: Introductionmentioning
confidence: 99%